(untitled) (Religious dialogue and cooperation, 2025)
This year’s paper for the Conference on “Religion and Globalization” has the theme: religion as a globalizer. The subject of the research is narrowed to the Problematic Question: How do integrist and integralist elements in major world religions stimulate globalization processes, and how is the globalization of national cultures into large civilizational wholes implemented through religious-integralist tendencies? The aim of the research is to point out the strong connection between religious integrism, cultural-political integralism and the globalization of national cultures into unique spiritual civilizations. The methods that will be used in the research are: observation method, cross-cultural method, comparative approach, content analysis... Practical contributions: in the area of interreligious tolerance, interfaith cooperation and intercultural dialogue. Scientific contribution: understanding the significance of the social background of religious integralism, researching the globalization of local and national cultures, deepening cognitive insights into the relationship: religion → culture → globalization. Social significance, primarily, in the advancement of scientific disciplines: sociology of religion, civilization studies and cultural studies.